Comments on the evolution of social, economic and cultural rights in Peru and the scope of its judiciability - Espinosa-Saldaña Barrera, Eloy (2015)
Are social, economic and cultural rights really enforceable rights? Is their nature different from those of the civil and political rights? What does our Constitution   state on the matter? What is the posture that national and international jurisprudence have adopted regarding the issue?In the article at hand, the  authors challenge the common conception about those rights, and analyze the work done by the Peruvian Constitutional Court on the matter.